Diversity of entomopathogenic fungi in rainforests of Chiang Mai Province, Thailand - Aung, O. M.; Soytong, K.; Hyde, K. D. (My University, 2008)
A survey of entomopathogenic fungi was carried out in both conserved and disturbed rainforests and agricultural habitats in Chiang Mai Province. Dead insects, other arthropods, and soil samples were collected from 2005 to 2006 during the rainy seasons. Thirty-four entomogenous taxa belonging to 15 genera were encountered. Entomopathogenic fungi were dominated by Ophiocordyceps myrmecophila (22.6%) and O. unilateralis (13.8%) on ants. Species diversity on Homoptera was highest, followed by Lepidoptera and Hymenoptera. Highest species diversity was found in disturbed rainforests, followed by conserved rainforests and agricultural habitats. Cordyceps and Ophiocordyceps species contributed 74.7% of total taxa in conserved rainforests, 61.3% in disturbed forests but only 1.6% in agricultural habitats.
Keywords: Biodiversity; Host specificity; Insect order; Species diversity